Homozygous iMycCα transgenic mice as a model of plasma B-cell lymphomas. Issue 9 (29th July 2022) - Ferrad, Melissa; Ghazzaui, Nour; Issaoui, Hussein; Drouineau, Emilie; Oblet, Christelle; Marchiol, Tiffany; Cook-Moreau, Jeanne; Denizot, Yves
Abstract: The 3' regulatory region (3'RR) located downstream from the Cα gene is the conductor of transcription, accessibility, and remodeling of the IgH locus at mature B-cell stages. Convincing demonstrations of the essential contributions of the 3'RR in B-cell lymphomagenesis have been provided by mouse models which bring the oncogene c-Myc under the 3'RR transcriptional control. In this study, we developed a mouse model of CD138 + plasma B-cell lymphomas. If the KI of c-myc directly into Cα just 5' to the 3'RR in iMycCα mice produced B-cell lymphomas with low kinetics, we enforced c-myc production in iMycCα mice by the generation of homozygous c-myc transgenic mice. Our results show that homozygous iMycCα mice lead to a mouse model of plasma CD138 + B-cell lymphomas with interesting and wide transcriptomic similarities to human multiple myeloma and appropriated emergence kinetics that can be used to test new experimental therapeutic approaches.